Method for preparing carbon fiber composite material through interface modification
By performing high-temperature desalination, activation treatment and ultrasonic-assisted polyimide salt solution impregnation on carbon fibers, a polyimide coating with carboxyl groups is formed, which solves the problem of insufficient adhesion between carbon fibers and resins, and significantly improves the mechanical properties of the composite material.
Patent Information
- Application Number
- CN202411764768.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-04
- Publication Date
- 2025-03-04
AI Technical Summary
There is a significant difference between the actual strength of existing carbon fiber composite materials and the theoretical maximum strength, mainly due to insufficient interface adjustment and optimization, resulting in insufficient adhesion between carbon fiber and resin.
After high-temperature desalination and activation treatment, ultrasonic-assisted polyimide solution is impregnated to form a polyimide coating with carboxyl groups, increasing the polar functional groups on the surface of the carbon fiber and improving the chemical bonding between the carbon fiber and the resin.
The interface strength between carbon fiber and resin is significantly improved, and the mechanical properties of the composite material, including bending strength and interlayer shear strength.
Smart Images

Figure CN119552391A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of preparation of carbon fiber composite materials, and specifically relates to a method for preparing carbon fiber composite materials through interface modification. Background Art
[0002] Carbon fiber composite materials have been widely used in many fields due to their light weight, high strength, high temperature resistance, corrosion resistance and excellent mechanical properties. Especially in the field of aerospace, carbon fiber composite materials are not only used for satellite structures and carriers, but also widely used in aircraft structures, such as large passenger aircraft such as Airbus A380, A350 and Boeing 787, accounting for a significant proportion of the total weight of the structure. In addition, this material is also used in high-speed EMUs, rail transit and civil aviation, significantly improving the performance and efficiency of transportation tools. With the advancement of technology and the continuous expansion of application fields, carbon fiber composite materials have entered a new era of large-scale industrial applications, showing broad development prospects.
[0003] At present, there is a significant difference between the actual strength of carbon fiber resin composites and their theoretical maximum strength. The reason for this gap is effective interface adjustment and optimization. The interface is located in the connection area between carbon fiber and resin, which plays a decisive role in the effective load transfer between the two. The surface of carbon fiber is composed of non-polar, highly crystallized lamellar graphite structure, which gives carbon fiber high chemical stability. However, this chemical inertness reduces the bonding strength between carbon fiber and resin, which in turn limits the widespread application of carbon fiber resin composites.
[0004] Patent CN103590233B discloses a method for interfacial modification of carbon fiber by cryogenic treatment, which increases the surface roughness of the carbon fiber by placing the carbon fiber at a constant temperature of -100°C to -200°C, thereby improving the interfacial bonding performance between the carbon fiber and the resin. However, the disadvantage of this method is that it requires extremely high energy consumption to create a low-temperature environment, which is not conducive to environmental protection and large-scale application.
[0005] Patent CN113981697B discloses a method for surface modification of carbon fiber composite materials, which realizes non-destructive surface modification of carbon fiber by in-situ self-assembly of block copolymers on the surface of carbon fiber to form an ordered nanostructure. By designing the functional characteristics of each molecular segment of the block polymer, the molecular segment that can be conjugated and enhanced with the carbon fiber surface and the molecular segment that is compatible with the matrix resin are combined to form a specific block copolymer, thereby significantly improving the interface bonding of the composite material. However, this method is relatively complicated and the preparation cycle of the copolymer is long.
[0006] Therefore, how to better perform interface modification on carbon fiber has become one of the problems to be solved urgently in this field. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a method for preparing a carbon fiber composite material by interface modification, so as to provide a carbon fiber composite material with good mechanical properties.
[0008] In order to solve the above technical problems, the present invention adopts the following technical scheme: the carbon fiber is sequentially subjected to high temperature desizing and activation treatment to prepare desizing carbon fiber activated by hydrogen peroxide, referred to as CFO; the CFO is placed in a polyimide salt solution for ultrasonic impregnation to prepare CFO-PAAs, and finally the CFO-PAAs is subjected to high temperature vacuum treatment to prepare CFO-PI-COOH. This method increases the number of polar functional groups on the surface of the carbon fiber, increases the chemical bonding between the carbon fiber and the resin, and constructs a stable interface, thereby achieving the purpose of the present invention.
[0009] The specific technical solutions of the present invention are as follows: A method for preparing a carbon fiber composite material by interface modification, the steps are as follows: (1) Desizing the carbon fiber at high temperature, the carbon fiber desizing treatment temperature is 200-500 ° C, and the time is 0.5-5h; The preferred carbon fiber desizing treatment time is 1.5-3 hours, and the carbon fiber desizing temperature is 300-400°C.
[0010] (2) Activating and soaking the desized carbon fiber in a hydrogen peroxide solution with a mass concentration of 5-30%, the soaking time is not less than 30 minutes, and the soaking temperature is 50°C-65°C to obtain CFO; preferably, a hydrogen peroxide solution with a mass concentration of 30% is used.
[0011] (3) Mixing 4,4-diaminodiphenyl ether and 3,5-diaminobenzoic acid in a certain molar ratio in N,N-dimethylacetamide and stirring under a nitrogen atmosphere; adding pyromellitic anhydride to the above solution and stirring at 0-20° C. to obtain a polyimide acid solution of a certain concentration; The molar ratio of 4,4-diaminodiphenyl ether, 3,5-diaminobenzoic acid and pyromellitic anhydride is 50-90:10-50:100, and the mass fraction of the polyimide acid solution finally obtained is 0.2%-5%.
[0012] (4) adding triethylamine to the polyimide acid solution obtained in step (3) above, and stirring at room temperature to obtain a polyimide salt solution; the molar ratio of triethylamine to pyromellitic anhydride in step (3) is 100:10-50; (5) subjecting CFO to ultrasonic treatment in the polyimide salt solution obtained in the previous step for a certain period of time to obtain CFO-PAAs, wherein the ultrasonic immersion time of CFO in the polyimide salt solution is 1-180 min; The mass ratio of CFO to polyimide salt solution is 1:30, the ultrasonic frequency is 50 kHz, and the temperature is controlled at 40° C. The ultrasonic immersion time is 10-60 min, and more preferably 20-40 min.
[0013] (6) CFO-PAAs was placed in a high-temperature vacuum oven and heated at 120 °C for 1 h, 200 °C for 1 h, and 300 °C for 1 h, respectively, to finally obtain CFO-PI-COOH.
[0014] After the treatment in step (1) in the above steps, the sizing agent on the surface of the carbon fiber is removed, which facilitates the subsequent modification of the carbon fiber. The carbon fiber is one of T300, T600, T700, T800, and T1000, or a mixture of several thereof.
[0015] After the treatment in step (2), the surface of the carbon fiber will produce more hydroxyl active groups due to the etching effect of hydrogen peroxide, providing connection sites for the subsequent grafting of polyimide coating.
[0016] Step (3) and step (4) are a process for preparing a surface modifier precursor. In this process, a precursor of the modifier, polyimide salts (PAAs), are prepared. Polyimide salts are selected because they are easier to store than polyimide acids and have higher activity, which facilitates the subsequent combination with CFO.
[0017] Step (5) is to introduce the surface modifier into the carbon fiber surface by immersing the carbon fiber in a polyimide salt solution for ultrasonic treatment. During the ultrasonic impregnation process, on the one hand, the segment dynamics and conformational evolution of the polyimide salt molecular chain are accelerated through the work-heat conversion effect, so that the polyimide salt molecular chain breaks free from the constraints of intermolecular interactions and promotes the diffusion of the polyimide salt molecular chain into the carbon fiber grooves; on the other hand, a cavitation effect can be generated during the ultrasonic impregnation process, so that the air molecules trapped in the carbon fiber gaps are removed, which is conducive to the full impregnation of the polyimide salt on the carbon fiber surface.
[0018] The purpose of step (6) is to further heat-treat the modifier on the surface of the carbon fiber, thereby changing its structure to PI-COOH. The PI-COOH coating contains a large number of carboxyl groups that can form ester bonds with the hydroxyl groups generated in step (2), thereby constructing a stable coating on the carbon fiber.
[0019] After obtaining CFO-PI-COOH, it can be used together with polyimide resin to prepare a composite material. Since the coating on CFO is similar to the molecular structure of polyimide resin, based on the principle of similar compatibility, the interface strength of the carbon fiber and polyimide resin composite material can be improved.
[0020] The beneficial effects of adopting the above technical solution are: 1) A polyimide coating with carboxyl groups was prepared on the surface of desized and activated carbon fibers by ultrasonic-assisted method and thermal curing method. The carboxyl groups on the surface of carboxylated polyimide can not only increase the chemical bonding between the coating and the carbon fibers, but also increase the physical interaction between the matrix resins, thereby building a stable connection between the carbon fibers and the polyimide resin.
[0021] 2) During the ultrasonic impregnation process, on the one hand, the segment dynamics and conformational evolution of the polyimide salt molecular chain are accelerated through the work-heat conversion effect, so that the polyimide salt molecular chain breaks free from the constraints of intermolecular interactions and promotes the diffusion of the polyimide salt molecular chain into the carbon fiber grooves; on the other hand, a cavitation effect can be generated during the ultrasonic impregnation process, so that the air molecules trapped in the carbon fiber gaps are eliminated, which is beneficial to the full impregnation of the polyimide salt on the carbon fiber surface.
[0022] The above two aspects can make the subsequently obtained polyimide coating and the carbon fiber surface closely fit, thereby constructing a stable interface between the carbon fiber and the polyimide resin, thereby improving the mechanical properties of the carbon fiber resin composite material. In addition, the above method of the present invention also has the advantages of easy operation and the like. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is the morphology of T300 carbon fiber after desizing in Example 1; Figure 2 This is the morphology of CFO-PI-COOH prepared in Example 1. DETAILED DESCRIPTION
[0024] The following embodiments are further explanations of the present invention, but are not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0025] The carbon fibers applicable to the present invention include any one or a mixture of T300, T600, T700, T800 and T1000, and the applicable resin matrix includes any one or any combination of epoxy resin, polyimide resin, phenolic resin, polyester resin, bismaleimide resin and polyamide resin. The technical scheme of the present invention is described in detail below by taking T300 carbon fiber and polyimide resin as examples. Among them, CFO refers to desizing carbon fiber activated by hydrogen peroxide; CFO-PI-COOH refers to CFO with a polyimide coating.
[0026] Unless otherwise specified, the materials and reagents used were commercially available products.
[0027] Example 1 A method for preparing a carbon fiber composite material by interface modification, comprising the following steps: (1) The undesized T300 carbon fiber was placed in a high temperature oven and subjected to high temperature desizing treatment at 340 °C for 2.5 h. The morphology of the desizing T300 carbon fiber is shown in the figure. Figure 1 shown.
[0028] (2) A 30% hydrogen peroxide solution was prepared, the desized carbon fiber was placed in the solution, and activated at 60°C for 4 hours to obtain CFO.
[0029] (3) preparing a polyimide acid solution, wherein the molar ratio of 4,4-diaminodiphenyl ether, 3,5-diaminobenzoic acid, and pyromellitic anhydride in the polyimide acid salt solution is 80:20:100; the total mass of the raw materials is 0.2% of the total mass of the solvent and the reactants. The specific operation is as follows: First, add 150 ml of dimethylacetamide solution into a 300 ml three-necked flask; control the temperature at 3°C and introduce nitrogen to maintain an inert gas atmosphere; then add 4,4-diaminodiphenyl ether and 3,5-diaminobenzoic acid to the above solution at the same time and stir for 5 minutes under a nitrogen atmosphere; then add pyromellitic anhydride to the above solution and stir for 8 hours under a nitrogen atmosphere to obtain a polyimide acid solution.
[0030] (4) triethylamine was added to the polyimide acid solution, and the mixture was stirred at 25° C. for 3 h to obtain a polyimide salt solution, wherein the molar ratio of triethylamine to unreacted pyromellitic anhydride was 100:30.
[0031] (5) CFO was placed in a prepared polyimide salt solution, wherein the mass ratio of CFO to the polyimide salt solution was 1:30, and ultrasonic treatment was performed for 20 min at a temperature of 40 °C and a power of 50 kHz to obtain CFO-PAAs.
[0032] (6) CFO-PAAs were placed in a high-temperature vacuum drying oven and treated at 120°C, 200°C, and 300°C for 60 min, 60 min, and 60 min, respectively, to obtain CFO-PI-COOH.
[0033] The morphology of CFO-PI-COOH obtained in the previous step is as follows Figure 2 As shown, according to Figure 1 and Figure 2 By comparing the above steps, we can see that PI-COOH is fully wrapped on the surface of carbon fiber. Figure 2It can be seen that there is a more obvious polymer film layer on the fiber surface, which is smoother and contains rich carboxyl groups, thereby improving the chemical bonding between the carbon fiber and the resin, building a bridge between the carbon fiber and the polyimide resin, and improving the interface bonding strength between the carbon fiber and the resin.
[0034] The inventor brushed the above-mentioned CFO-PI-COOH with polyimide resin (selected from KH320N) and woven it into cloth, and prepared the prepreg by laying layers. In this embodiment, the number of layers is ten. In the prepreg, the mass fraction of polyimide resin is 40%. The above-mentioned prepreg is quickly placed in a preheated mold and molded into a plate in a flat vulcanizer. The molding temperature is 120°C, 200°C, 280°C, and 320°C, and the time is 60min, 60min, 40min, and 60min respectively. After completion, take it out and cool it to room temperature to obtain the polyimide resin-based T300 carbon fiber reinforced composite material of this embodiment.
[0035] The polyimide resin-based T300 carbon fiber reinforced composite material of this embodiment was made into a standard specimen, and its mechanical properties were tested according to GB / T 1449-2005 and JC / T 773-2010 standards. The test results were: bending strength 955 MPa, interlaminar shear strength 65 MPa.
[0036] Comparative Example 1 A method for preparing a carbon fiber composite material by interface modification, the steps are as follows: The undesized T300 carbon fiber is placed in a high-temperature oven and subjected to a high-temperature desizing treatment at 340°C for 2.5 hours; the desized CFO is brushed with a polyimide resin (selected from KH320N) in the same manner as in Example 1 and then woven into a cloth, and a prepreg is prepared by laying. The number of layers in this comparative example is also ten, and the prepreg is prepared by laying; the above prepreg is quickly placed in a preheated mold and molded into a plate in a flat vulcanizer, and the molding temperatures are 120°C, 200°C, 280°C, and 320°C, and the time is 60min, 60min, 40min, and 60min, respectively. After completion, take it out and cool it to room temperature, that is, the polyimide resin-based T300 carbon fiber reinforced composite material of this comparative example is prepared.
[0037] The polyimide resin-based T300 carbon fiber reinforced composite material of this comparative example was made into a standard specimen, and the mechanical properties thereof were tested according to GB / T 1449-2005 and JC / T 773-2010 standards. The test results were: bending strength: 748.85 MPa, interlaminar shear strength: 53.48 MPa.
[0038] By comparison, it can be seen that the flexural strength and interlaminar shear strength of the polyimide resin-based T300 carbon fiber reinforced composite material obtained in Example 1 are respectively improved by about 12.1% and 27.53% compared with the composite material prepared from the untreated carbon fiber in Comparative Example 1. Significant progress has been made.
[0039] Example 2 A method for preparing a carbon fiber composite material by interface modification, comprising the following steps: (1) The undesized T300 carbon fiber was placed in a high-temperature oven and subjected to high-temperature desizing treatment at 340 °C for 2.5 h.
[0040] (2) A 30% hydrogen peroxide solution was prepared, the desized carbon fiber was placed in the solution, and activated at 60°C for 4 hours to obtain CFO.
[0041] (3) Prepare a polyimide acid solution, wherein the molar ratio of 4,4-diaminodiphenyl ether, 3,5-diaminobenzoic acid, and pyromellitic anhydride in the polyimide acid salt solution is 70:30:100; the total mass of the raw materials is 0.5% of the total mass of the solvent and the reactants. The specific preparation process is the same as that in Example 1, and the inventors will not repeat it here.
[0042] (4) Add triethylamine to the polyimide acid solution, and stir at 25° C. for 3 h to obtain a polyimide salt solution, wherein the molar ratio of triethylamine to unreacted pyromellitic anhydride is 60:30.
[0043] (5) CFO was placed in a prepared polyimide salt solution, wherein the mass ratio of CFO to the polyimide salt solution was 1:30, and ultrasonicated for 20 min to obtain CFO-PAAs. The ultrasonic temperature was 40 °C and the power was 50 kHz.
[0044] (6) CFO-PAAs were placed in a high-temperature vacuum drying oven and treated at 120°C, 200°C, and 300°C for 60 min, 60 min, and 60 min, respectively, to obtain CFO-PI-COOH.
[0045] The above CFO-PI-COOH was brushed with polyimide resin and woven into cloth, and then the polyimide resin-based T300 carbon fiber reinforced composite material was prepared in the same manner as in Example 1, and then the mechanical properties were tested in the same manner as in Example 1 according to GB / T 1449-2005 and JC / T 773-2010 standards. The test results were: bending strength 896.52MPa, interlaminar shear strength 70.97MPa. Compared with the composite material prepared from the untreated carbon fiber in Comparative Example 1, they were improved by about 19.72% and 32.70%, respectively.
[0046] Example 3 A method for preparing a carbon fiber composite material by interface modification, comprising the following steps: (1) The undesized T300 carbon fiber was placed in a high-temperature oven and subjected to high-temperature desizing treatment at 340 °C for 2.5 h.
[0047] (2) A 30% hydrogen peroxide solution was prepared, the desized carbon fiber was placed in the solution, and activated at 60°C for 4 hours to obtain CFO.
[0048] (3) Prepare a polyimide acid solution, wherein the molar ratio of 4,4-diaminodiphenyl ether, 3,5-diaminobenzoic acid, and pyromellitic anhydride in the polyimide acid salt solution is 80:20:100; the total mass of the raw materials is 1% of the total mass of the solvent and the reactants. The specific preparation process is the same as that in Example 1, and the inventors will not repeat it. The specific preparation process is the same as that in Example 1, and the inventors will not repeat it.
[0049] (4) Add triethylamine to the polyimide acid solution, and stir at 25° C. for 3 h to obtain a polyimide salt solution, wherein the molar ratio of triethylamine to unreacted pyromellitic anhydride is 60:30.
[0050] (5) CFO was placed in a prepared polyimide salt solution, wherein the mass ratio of CFO to the polyimide salt solution was 1:30, and ultrasonic treatment was performed for 20 min to obtain CFO-PAAs. The ultrasonic temperature was 40 °C and the power was 50 kHz.
[0051] (6) CFO-PAAs were placed in a high-temperature vacuum drying oven and treated at 120°C, 200°C, and 300°C for 60 min, 60 min, and 60 min, respectively, to obtain CFO-PI-COOH.
[0052] The above CFO-PI-COOH was brushed with polyimide resin and woven into cloth, and then the polyimide resin-based T300 carbon fiber reinforced composite material was prepared in the same manner as in Example 1, and then the mechanical properties were tested in the same manner as in Example 1 according to GB / T 1449-2005 and JC / T 773-2010 standards. The test results were: bending strength 966.84MPa, interlaminar shear strength 76MPa. Compared with the composite material prepared from the untreated carbon fiber in Comparative Example 1, they were improved by about 29.11% and 42.1%, respectively.
[0053] Example 4 A method for preparing a carbon fiber composite material by interface modification, comprising the following steps: (1) The undesized T300 carbon fiber was placed in a high-temperature oven and subjected to high-temperature desizing treatment at 250 °C for 5 h.
[0054] (2) A 20% hydrogen peroxide solution was prepared, the desized carbon fiber was placed in the solution, and activated at 60°C for 8 hours to obtain CFO.
[0055] (3) preparing a polyimide acid solution, wherein the molar ratio of 4,4-diaminodiphenyl ether, 3,5-diaminobenzoic acid and pyromellitic anhydride in the polyimide acid salt solution is 60:40:100; the total mass of the raw materials is 1.2% of the total mass of the solvent and the reactants; the specific preparation process is the same as that in Example 1, and the inventors will not repeat it here.
[0056] (4) Add triethylamine to the polyimide acid solution, and stir at 25° C. for 3 h to obtain a polyimide salt solution, wherein the molar ratio of triethylamine to unreacted pyromellitic anhydride is 60:30.
[0057] (5) CFO was placed in a prepared polyimide salt solution, wherein the mass ratio of CFO to the polyimide salt solution was 1:30, and ultrasonicated for 30 min to obtain CFO-PAAs. The ultrasonic temperature was 40 °C and the power was 50 kHz.
[0058] (6) CFO-PAAs were placed in a high-temperature vacuum drying oven and treated at 120°C, 200°C, and 300°C for 60 min, 60 min, and 60 min, respectively, to obtain CFO-PI-COOH.
[0059] The above CFO-PI-COOH was brushed with polyimide resin and woven into cloth, and then the polyimide resin-based T300 carbon fiber reinforced composite material was prepared in the same manner as in Example 1, and then the mechanical properties were tested in the same manner as in Example 1 according to GB / T 1449-2005 and JC / T 773-2010 standards. The test results were: 1098.63MPa, interlaminar shear strength 79.97MPa. Compared with the composite material prepared from the untreated carbon fiber in Comparative Example 1, they were improved by about 46.71% and 49.53%, respectively.
[0060] Example 5 A method for preparing a carbon fiber composite material by interface modification, comprising the following steps: (1) The undesized T300 carbon fiber was placed in a high-temperature oven and subjected to high-temperature desizing treatment at 400 °C for 1 h.
[0061] (2) A 15% hydrogen peroxide solution was prepared, the desized carbon fiber was placed in the solution, and activated at 60°C for 10 h to obtain CFO.
[0062] (3) preparing a polyimide acid solution, wherein the molar ratio of 4,4-diaminodiphenyl ether, 3,5-diaminobenzoic acid and pyromellitic anhydride in the polyimide acid salt solution is 50:50:100; the total mass of the raw materials is 1% of the total mass of the solvent and the reactants; the specific preparation process is the same as that in Example 1, and the inventors will not repeat it here.
[0063] (4) Add triethylamine to the polyimide acid solution, and stir at 25° C. for 3 h to obtain a polyimide salt solution, wherein the molar ratio of triethylamine to unreacted pyromellitic anhydride is 60:30.
[0064] (5) CFO was placed in a prepared polyimide salt solution, wherein the mass ratio of CFO to the polyimide salt solution was 1:30, and ultrasonicated for 20 min to obtain CFO-PAAs. The ultrasonic temperature was 40 °C and the power was 50 kHz.
[0065] (6) CFO-PAAs were placed in a high-temperature vacuum drying oven and treated at 120°C, 200°C, and 300°C for 60 min, 60 min, and 60 min, respectively, to obtain CFO-PI-COOH.
[0066] The above CFO-PI-COOH was brushed with polyimide resin and woven into cloth, and then the polyimide resin-based T300 carbon fiber reinforced composite material was prepared in the same manner as in Example 1, and then the mechanical properties were tested in the same manner as in Example 1 according to GB / T 1449-2005 and JC / T 773-2010 standards. The test results were: bending strength 940.48MPa, interlaminar shear strength 68.97MPa. Compared with the composite material prepared from the untreated carbon fiber in Comparative Example 1, they were improved by about 25.59% and 28.97%, respectively.
[0067] Example 6 A method for preparing a carbon fiber composite material by interface modification, comprising the following steps: (1) The undesized T300 carbon fiber was placed in a high-temperature oven and subjected to high-temperature desizing treatment at 350 °C for 2.5 h.
[0068] (2) A 30% hydrogen peroxide solution was prepared, the desized carbon fiber was placed in the solution, and activated at 60°C for 5 hours to obtain CFO.
[0069] (3) preparing a polyimide acid solution, wherein the molar ratio of 4,4-diaminodiphenyl ether, 3,5-diaminobenzoic acid and pyromellitic anhydride in the polyimide acid salt solution is 60:40:100; the total mass of the raw materials is 0.5% of the total mass of the solvent and the reactants; the specific preparation process is the same as that in Example 1, and the inventors will not repeat it here.
[0070] (4) Add triethylamine to the polyimide acid solution, and stir at 25° C. for 3 h to obtain a polyimide salt solution, wherein the molar ratio of triethylamine to unreacted pyromellitic anhydride is 60:30.
[0071] (5) CFO was placed in a prepared polyimide salt solution, wherein the mass ratio of CFO to the polyimide salt solution was 1:30, and ultrasonicated for 40 min to obtain CFO-PAAs. The ultrasonic temperature was 40 °C and the power was 50 kHz.
[0072] (6) CFO-PAAs were placed in a high-temperature vacuum drying oven and treated at 120°C, 200°C, and 300°C for 60 min, 60 min, and 60 min, respectively, to obtain CFO-PI-COOH.
[0073] The above CFO-PI-COOH was brushed with polyimide resin and woven into cloth, and then the polyimide resin-based T300 carbon fiber reinforced composite material was prepared in the same manner as in Example 1, and then the mechanical properties were tested in the same manner as in Example 1 according to GB / T 1449-2005 and JC / T 773-2010 standards. The test results were: bending strength 1140.87MPa, interlaminar shear strength 81.49MPa. Compared with the composite material prepared from the untreated carbon fiber in Comparative Example 1, they were improved by about 52.35% and 52.37%, respectively.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a carbon fiber composite material by interface modification, characterized in that: Here are the steps: (1) Desizing the carbon fiber at high temperature, the carbon fiber desizing treatment temperature is 200-500 ° C, and the time is 0.5-5 h; (2) Activating and soaking the desized carbon fiber with a hydrogen peroxide solution having a mass concentration of 5-30%, the soaking time being not less than 30 minutes and the soaking temperature being 50°C-65°C to obtain CFO; (3) Mixing 4,4-diaminodiphenyl ether and 3,5-diaminobenzoic acid in a certain molar ratio in N,N-dimethylacetamide and stirring under a nitrogen atmosphere; adding pyromellitic anhydride to the above solution and stirring at 0-20° C. to obtain a polyimide acid solution with a mass fraction of 0.2%-5%; (4) adding triethylamine to the polyimide acid solution obtained in step (3) above, and stirring at room temperature to obtain a polyimide salt solution; the molar ratio of triethylamine to pyromellitic anhydride in step (3) is 100:10-50; (5) subjecting CFO to ultrasonic treatment in the polyimide salt solution obtained in the previous step for a certain period of time to obtain CFO-PAAs, wherein the ultrasonic immersion time of CFO in the polyimide salt solution is 1-180 min; (6) CFO-PAAs was placed in a high-temperature vacuum oven and heated at 120 °C for 1 h, 200 °C for 1 h, and 300 °C for 1 h, respectively, to finally obtain CFO-PI-COOH.
2. The method for preparing a carbon fiber composite material by interface modification according to claim 1, characterized in that: In step (1), the carbon fiber desizing treatment time is 1.5-3 hours, and the carbon fiber desizing temperature is 300-400°C.
3. The method for preparing a carbon fiber composite material by interface modification according to claim 1, characterized in that: In step (2), a hydrogen peroxide solution with a mass concentration of 30% is used.
4. The method for preparing a carbon fiber composite material by interface modification according to claim 1, characterized in that: In step (3), the molar ratio of 4,4-diaminodiphenyl ether, 3,5-diaminobenzoic acid and pyromellitic anhydride is 50-90:10-50:
100.
5. The method for preparing a carbon fiber composite material by interface modification according to claim 1, characterized in that: In step (5), the mass ratio of CFO to polyimide salt solution is 1:30, the ultrasonic frequency is 50 kHz, and the temperature during ultrasound is controlled at 40°C.
6. The method for preparing a carbon fiber composite material by interface modification according to claim 1 or 5, characterized in that: The ultrasonic immersion time in step (5) is 10-60 min.
7. The method for preparing a carbon fiber composite material by interface modification according to claim 6, characterized in that: The ultrasonic immersion time in step (5) is 20-40 minutes.
8. The method for preparing a carbon fiber composite material by interface modification according to claim 6, characterized in that: The carbon fiber is one of T300, T600, T700, T800 and T1000 or a mixture of several of them.
Citation Information
Patent Citations
A method for interfacial modification of carbon fibers through cryogenic treatment
CN103590233B
A method for modifying the surface and interface of carbon fiber and the modified carbon fiber therefrom
CN113981697B
Corona-resistant polyimide / silica nano composite film and preparation method thereof
CN103554533A
Polyimide / nano-silica composite porous film containing carboxyl structure and preparation method thereof
CN105449142A
Preparation method of carbon fiber enhanced polyimide based composite material
CN109265998A
Cited By
Nano indium-iron microcrystalline adhesive and curing process
CN120442199A
Carbon fiber connecting glue and curing process
CN122648042A